Diagnostic value of dynamic contrast-enhanced CT with perfusion imaging in the quantitative assessment of tumor response to sorafenib in patients with advanced hepatocellular carcinoma: A feasibility study. Issue 90 (May 2017) - Ippolito, Davide; Querques, Giulia; Okolicsanyi, Stefano; Franzesi, Cammillo Talei; Strazzabosco, Mario; Sironi, Sandro
Highlights: Perfusion computed tomography is a well-recognized technique that enables depiction of tumor vascular physiology having the ability to detect regional and global alterations in organ blood flow, in addition to being non-invasive and fast. The quantitative measurement of hepatic perfusion has the potential to provide important information in the assessment and management of advanced HCC lesion and in the determination of their outcome. After treatment with sorafenib in the group that responded to therapy we observed a significant decrease of all perfusion parameters, indirectly reflecting the angiogenic factor's expression. Moreover, a 33% reduction of HP in HCC lesions was associated with an increased rate of response to treatment. Considering the different mRECIST categories, a significantly reduction of perfusion parameters was obtained in the group with complete response (79%) compared to the group with partial response or stable disease (16%), demonstrating the prognostic significance of perfusion value. While in patients that did not respond to sorafenib, p-CT parameters showed, as expected, a trend toward an increase of the values related to arterial vascularization. Perfusion CT could be integrated into the current computed tomographic protocols, offering useful information for the optimization of individualized treatment. Abstract: Purpose: To investigate the feasibility of perfusion-CT (p-CT) measurements in quantitative assessment of hemodynamic changes related to sorafenib in patients with advanced hepatocellular carcinoma (HCC). Materials and methods: Twenty-two patients with advanced HCC underwent p-CT study (256-MDCT scanner) before and 2 months after sorafenib administration. Dedicated perfusion software generated a quantitative map of arterial and portal perfusion and calculated the following perfusion parameters in target liver lesion: hepatic perfusion (HP), time-to-peak (TTP), blood volume (BV), arterial perfusion (AP), and hepatic perfusion index (HPI). After the follow-up scan, patients were categorized as responders and non-responders, according to mRECIST. Perfusion values were analyzed and compared in HCC lesions and in the cirrhotic parenchyma ( n  = 22), such as between baseline and follow-up in progressors and non-progressors. Results: Before treatment, all mean perfusion values were significantly higher in HCC lesions than in the cirrhotic parenchyma (HP 47.8 ± 17.2 vs 13.3 ± 6.3 mL/s per 100 g; AP 47.9 ± 18.1 vs 12.9 ± 10.7 mL/s; p  < 0.001). The group that responded to sorafenib ( n  = 17) showed a significant reduction of values in HCC target lesions after therapy (HP 29.2 ± 23.3 vs 48.1 ± 15.1; AP 29.4 ± 24.6 vs 49.2 ± 17.4; p  < 0.01), in comparison with the non-responder group ( n  = 5) that demonstrated no significant variation before and after treatment of HP (46.9 ± 25.1 vs 46.7 ± 24.1) and AP (43.4 ± 21.7 vs 43.5 ± 24.6). Among the responder group, HP percentage variation (Δ) in target lesions, during treatment, showed a significantly different ( p  = 0.04) ΔHP in the group with complete response (79%) compared to the group with partial response or stable disease (16%). Conclusions: p-CT technique can be used for HCC quantitative assessment of changes related to anti-angiogenic therapy. Identification of response predictors might help clinicians in selection of patients who may benefit from targeted-therapy allowing for optimization of individualized treatment.